Targeted Delivery of Glucan Particle Encapsulated Gallium Nanoparticles Inhibits HIV Growth in Human Macrophages. (14th November 2016) - Soto, Ernesto R.; O'Connell, Olivia; Dikengil, Fusun; Peters, Paul J.; Clapham, Paul R.; Ostroff, Gary R.
Abstract : Glucan particles (GPs) are hollow, porous 3–5  μ m microspheres derived from the cell walls of Baker's yeast ( Saccharomyces cerevisiae). The 1, 3- β -glucan outer shell provides for receptor-mediated uptake by phagocytic cells expressing β -glucan receptors. GPs have been used for macrophage-targeted delivery of a wide range of payloads (DNA, siRNA, protein, small molecules, and nanoparticles) encapsulated inside the hollow GPs or bound to the surface of chemically derivatized GPs. Gallium nanoparticles have been proposed as an inhibitory agent against HIV infection. Here, macrophage targeting of gallium using GPs provides for more efficient delivery of gallium and inhibition of HIV infection in macrophages compared to free gallium nanoparticles.